Participation in tripartite cooperation - Klaus Bolz; Peter Plötz (Intereconomics, 1975)
The following article is an excerpt from a study written by the authors on behalf of the UNCTAD. It is based on the experiences of German enterprises which have been participating in cooperation projects with CMEA-states and developing countries.
Keywords: 330; Germany